Determine the Prevalence of High Thrombolysis in Myocardial Infarction (TIMI) Risk Scores and Complications Associated to High TIMI Score in Patients Presented with Acute ST Elevation Myocardial Infarction (Medical Forum Monthly, 2024)
Objective: To determine the prevalence of high thrombolysis in myocardial Infarction (TIMI) risk score and complications associated to high TIMI risk score among patients presented with acute ST elevation myocardial infarction.Study Design: Cross sectional study.Place and Duration of Study: This study was conducted at the Department of Cardiology, Mayo Hospital, Lahore from January 2018 to December 2018.Materials and Methods: A total of 290 patients of both genders with ages 35 to 80 years presented with acute myocardial infarction were included. Patients detailed medical history including age, sex and residence were recorded. Thrombolysis in myocardial infarction (TIMI) risk score was calculated for each patient. Follow-up was taken during the hospital stay and after discharge. Complications were recorded on follow-upResults: From all the patients high TIMI score was found in 34.48% patients. There were 70% males and 30% females with mean age 54.25+12.65 years. High TIMI score 100 (34.48%) patients had score above 8 and 190 (65.52%) had score less than 8. Complications were ventricular fibrillation, VT, AF, heart block, cardiogenic shock and pulmonary edema in 17%, 13%, 2%, 7%, 24% and 24% patients respectively. 15% patients were died during hospital stay. 28% patients had post-infarct angina, 9% patients had stroke and 28% patients treated revascularization.Conclusion: Frequency of high TIMI score is high in our setting and we patients with increase score had high risk of complications and mortality.